La santa Juana de Tirso de Molina: justicia humana, justicia divina, justicia poética - Isabel Ibáñez (E-Spania)
In a comedia structured around the unfair trial of Joan of the Cross, it’s surprising that the subject of trial, duplicated in other judgments concerning various characters is not exploited from dramatic and theatrical standpoint, except for the model of “solomonian judgment”. That’s even more obvious that, in the background we can see the Lope’s Fuenteovejuna as “hypotext”.The dramatic options of the Santa Juana II turn out that they discredit the Lope’s judicial proposition.